Fasciola gigantica التغيرات المرضية الناجمة عن تغذية الفئران المختبرية على أكباد الجاموس المصابة بطفيلي - منال إسماعيل خليل (University of Thi-Qar Journal of Science, 2019)
The present study has proven that the livers of infected animals by Fasciola giganticashould not be addible for human being in even they cooked.The present study involved use of (treated and untreated with heat) liver squash of infectedBuffalo with F. gigantica, the results showed that feeding on infected livers caused congestion andincrease in number of Kuffer‘s Cells in blood vessels in dosing mice with liver squash treated withheat.The study revealed also congestion of blood vessels and sinusoids, in addition toaggregation of Kuffer‘s Cells beside blood vessels and increase in their number andhyperpigmentation of nuclei as well as enlargement of liver cells in the mice administered withliver squash untreated with heat.